History of the Development of Islamic Education in Indonesia (A Case Study of Old Order and New Order Governments (1945-1998) - Zulkifli Tanjung (STAI Hubbulwathan Duri, 2022)
The development of Islamic educational institutions in Indonesia has undergone the different developments in accordance with the period of government politics. The old order era and the new order era, for example, have their own dynamics of development. This study analyzes the development of Islamic education that occurred during the Old Order and the New Order governments (1945-1998). This research uses a historical approach which is based on literature study. Library research is a method of collecting data and information; from books, magazines, documents, journals, history books, and others. The results of this study indicate that: 1) The thought of Islamic education in the period of independent Indonesia was characterized by a dualistic education model: a) the education and teaching system in secular public schools did not recognize religious teachings, which was the legacy of the Dutch colonial government. b) Islamic education and teaching system that grows and develops in the Islamic community, both isolated-traditional and synthetic with a variety of educational patterns. 2) The practice of education from the time of Indonesia's independence until 1965 can be said to be heavily influenced by the Dutch education system. This colonial education practice continues to discriminate between the children of officials and ordinary children. 3) Islamic education has strengthened its position after entering and being inclusive in the national education system which is regulated in Law No. 2 of 1989 which further regulated a series of government regulations relating to education and then continued with the enactment of Law No. 20 of 2003. Meanwhile, the development of post-New Order Islamic education is a topic that needs further research.